Work Engagement As Mediator Between Quality Work of Life and Organizational Commitment in PT. XYZ - Muhammad Ramadhan; Rostiana Rostiana (Psychosophia: Journal of Psychology, Religion, and Humanity, 2022)
This research was conducted to find out the role of work engagement as a mediator between the quality of work life and organizational commitment. Participants in this study were 400 employees who worked at PT XYZ (One of the biggest Manufacture in Indonesia). In the implementation of the research conducted the dissemination of measuring tools of work quality, work engagement, and organizational commitment. The technique used to analyze the main data is to use regression analysis techniques using SPSS version 24.00. Based on the results of data processing it is known that the variables of work engagement and quality of work-life simultaneously affect the variables of organizational commitment with a coefficient of determination 0.541. Furthermore, it is known that work engagements variables can mediate the relationship between quality of work life variables and organizational commitments